DISRUPTION OF MACROECONOMICS ON ISLAMIC MUTUAL FUND - Jayaprawira, Acep Riana; Saiful, Saiful (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2021)
This study intends to investigate the disturbance of the cash supply, rupiah swapping scale, expansion, and Islamic Certificate of Bank Indonesia to the Net Asset Value of Islamic Mutual Funds. This examination is led by work area study by means of diary, book, and web media. Philosophy utilizes quantitative examination with the Vector Auto Regression/Vector Error Correction Model (VAR/VECM) research technique. The consequences of study shows that in the long haul, all factors impact Islamic common assets aside from the SBIS variable. In the aftereffects of the IRF test, in the event that there is a shock to the cash supply variable, the rupiah conversion scale, expansion, and SBIS, Islamic shared assets will react in a fluctuating way. The aftereffect of FEVD shows that the rupiah swapping scale variable has the biggest commitment to common assets on Islamic premise.